ANALISIS POTENSI KEBANGKRUTAN DENGAN MENGGUNAKAN ALTMAN SCORE PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013 – 2017 - Zulfikar Zulfikar; Fariyanti Fariyanti; Liana Febrianti (Politeknik Negeri Samarinda, 2019)
This study aims to determine the potential bankruptcies that occur in mining companies listed on the BEI by using the method of Altman Z”-Score modification. The object of research is a mining sector company listed on Indonesia Stock Exchange, the method used is the method Altman Z-Score Modification (1995) with the equation Z